2017
DOI: 10.12913/22998624/68460
|View full text |Cite
|
Sign up to set email alerts
|

FRICTION MODELING OF Al-Mg ALLOY SHEETS BASED ON MULTIPLE REGRESSION ANALYSIS AND NEURAL NETWORKS

Abstract: This article reports a proposed approach to a frictional resistance description in sheet metal forming processes that enables the determination of the friction coefficient value under a wide range of friction conditions, without performing timeconsuming experiments. The motivation for this proposal is the fact that there exists a considerable amount of factors that affect the friction coefficient value and as a result building analytical friction model for specified process conditions is practically impossible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Among all training pairs (162 input signals and the corresponding output signal), 10% [ 33 , 77 ] were randomly selected and included in the validation set. The moment the RMS error value of the validation set no longer decreases was adopted as the criterion for completing the network training process [ 33 , 77 ]: where z i is the expected signal of the output neuron for the i -th pattern, y i is the signal of the output neuron for the i -th pattern, N is the number of vectors in the training set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all training pairs (162 input signals and the corresponding output signal), 10% [ 33 , 77 ] were randomly selected and included in the validation set. The moment the RMS error value of the validation set no longer decreases was adopted as the criterion for completing the network training process [ 33 , 77 ]: where z i is the expected signal of the output neuron for the i -th pattern, y i is the signal of the output neuron for the i -th pattern, N is the number of vectors in the training set.…”
Section: Methodsmentioning
confidence: 99%
“…The prospects for the use of artificial intelligence in tribology have been discussed in the paper of Rosenkranz et al [ 32 ]. Lemu et al [ 33 ] applied radial basis function (RBF) ANNs to create a mathematical model of friction behaviour based on the results of the strip drawing test. They found that the back propagation algorithm is the most efficient learning algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of single point incremental forming, owing to the point contact of the tool with the sheet, there are more severe contact conditions than in conventional SMF [73]. Aluminium and titanium sheets show a much greater tendency towards galling compared to steel sheets [74,75].…”
Section: Lubricationmentioning
confidence: 99%
“…By changing the number of radial functions, the obtained results and the execution time of the plan are different [10,11]. Figure 6: RBF neural network [12] In RBF neural network, by changing the number of radial base functions, the obtained clustering rate is changed and the increase of the number of these functions is effective on its computation time. According to the obtained CCR, the best result in the number of radial functions is 15.…”
Section: Radial Base Function Neural Networkmentioning
confidence: 99%